Antes de Otranto: apontamentos para uma pré-história do gótico na literatura - Rossi, Aparecido Donizete [UNESP] (Universidade de Estado do Rio de Janeiro, 2014)
Departing from Ariovaldo Vidal’s statement, in his foreword to the Brazilian translation of The Castle of Otranto, that the Gothic sources were spread upon literary and social history waiting for someone (Horace Walpole) to collect them in order to create a new literary genre, and connecting imagination to such statement, my purpose in this paper is to make some notes on what would possibly be these sources referred by Vidal. By the means of thinking on the Darkness as a semi-concept, a perspective largely inspired in Fred Botting’s Gothic (2014), I intend to look for the origins of Gothic fiction in texts by Homer, Virgil, Dante, and Milton.

Partindo-se da observação de Ariovaldo Vidal, em sua apresentação à tradução brasileira de O castelo de Otranto, na qual o crítico afirma que as raízes do Gótico estavam espalhadas pela história literária e social esperando que alguém (Horace Walpole) as recolhesse para criar um novo gênero literário, e agregando a essa observação o imaginário, pretende-se realizar, no presente texto, alguns breves apontamentos sobre quais seriam, possivelmente, as raízes aos quais Vidal se refere. Recorrendo a uma reflexão sobre as Trevas como semi-conceito, em boa parte inspirada por Fred Botting em Gothic (2014), intenta-se buscar os primórdios da ficção gótica em textos de Homero, Virgílio, Dante e Milton.
Before Otranto: notes on a pré-history of the gothic in literature
Keywords: Gothic; Imagination; British Literature; Classic Literature; Gótico; Imaginário; Literatura inglesa; Literatura clássica